Strategies for Forming Student Discipline in Islamic Elementary Schools Malaysia: A Holistic Approach in Character Education - Mahmudulhassan; Muhammad Abuzar; Shikdar Mohammad Riazul; Obydur Rahman; Abdulrohim E-sor (Walidem Institute and Publishing (WIP), 2024)
This study aims to analyze the strategy of forming student discipline in Islamic Elementary Schools in Malaysia through a holistic approach to character education. The main focus of this research is to identify the methods and practices used by these schools in shaping student discipline, as well as how a holistic approach can support balanced and sustainable character development. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with teachers, principals, and parents of students, as well as through direct observation in several selected Islamic Elementary Schools in Malaysia. Data analysis was carried out using thematic analysis techniques to identify patterns and main themes related to discipline formation strategies. The results show that Islamic Elementary School students in Malaysia have adopted various discipline formation strategies that integrate Islamic values with the principles of character education. The holistic approach applied includes spiritual coaching, strengthening social relationships between students, and the application of fair and consistent discipline. The study also found that collaboration between schools and parents has an important role in shaping student discipline, with an emphasis on the values of togetherness, responsibility, and honesty. The novelty of this study lies in the disclosure of how a holistic approach to character education can have a positive impact on the formation of sustainable discipline in the primary school environment. The implications of this study show that a holistic approach that integrates religious, social, and emotional values can be an effective model in shaping student discipline in Islamic Elementary Schools. This research makes an important contribution to the development of student character education strategies in Islamic Elementary Schools in Malaysia and can be a reference for education practitioners in improving the quality of character education in other educational institutions.